Obstructive Sleep Apnea and Cardiovascular Risk: The Role of Dyslipidemia, Inflammation, and Obesity - Zdravkovic, Marija; Popadic, Viseslav; Klasnja, Slobodan; Milic, Natasa; Rajovic, Nina; Divac, Anica; Manojlovic, Andrea; Nikolic, Novica; Lukic, Filip; Rasiti, Esma; Mircetic, Katarina; Marinkovic, Djordje; et al. (Frontiers in Pharmacology, 2022)
Introduction: The present study aimed to establish the role of lipid abnormalities and inflammatory markers for developing cardiovascular risk, as well as to address the importance of obesity as a common comorbidity in patients with obstructive sleep apnea (OSA). Methods: The study was conducted as a prospective cohort study including 120 patients with newly diagnosed OSA between 2019 and 2020, at University Clinical Hospital Center “Bezanijska kosa”, Belgrade, Serbia. The diagnosis was established by polysomnography. In all patients, sociodemographic data, respiratory, lipid, and inflammatory parameters were collected and complete echocardiographic study and 24-hour blood pressure monitoring were performed. Results: The mean patient age was 55.7±13.8 years. Study population was mostly male (70.0%) and obese (56.7%). At least 30 apneas or hypopneas per hour were present in 39.0% of patients. A strong positive correlation was found between OSA severity and BMI (r=0.562, p<0.001), both associated with lipid, inflammatory and respiratory parameters, and cardiovascular profile of patients with OSA (p<0.05 for all). Echocardiographic study and 24-hour blood pressure monitoring parameters were in turn correlated with lipid and inflammatory markers (p<0.05 for all). Conclusion: The results of this study support the important role of dyslipidemia and inflammation, as well as coexistence of obesity in the pathogenesis of numerous conditions linked with an increased risk of cardiovascular morbidity and mortality in patients with OSA.